Reduction of Optimal Thermal Range in Aging Western Cherry Fruit Flies (Diptera: Tephritidae). Issue 1 (22nd June 2015) - Neven, Lisa G.
Abstract : The western cherry fruit fly is an economically important pest of sweet cherries in the western United States. The potential of this pest to establish and spread in areas in which it is not currently present has been the focus of recent research. Most published information on the thermal tolerance and optimal thermal range of this pest has focused primarily on the diapausing pupae and predictive phenology models. Microrespirometry and differential calorimetry can be useful tools in describing the thermotolerance and optimal thermal range of insects. This methodology was employed to investigate the effects of western cherry fruit fly adult age on the optimal thermal range. Newly emerged flies exhibited the widest optimal thermal range spanning from 6.6 to 42.2°C for a total range of 35.8°C during heating scans of 0.4°C/min from 2 to 50°C. This range diminished as the flies aged, with the shortest span observed with 28-d-old flies ranging from 10.5 to 37.8°C, a span of 27.2°C. Measurements of heat rate and oxygen consumption at isothermal, or static, temperatures indicated that all flies could survive exposure to 40°C for at least 20 min, and that metabolism was greatly reduced, with a concomitant reduction in oxygen consumption rate at 40 to 42°C. All flies exhibited a heat rate and oxygen consumption rate of zero when exposed to 45 and 50°C. The loss of thermotolerance in adult flies can influence its ability to establish and spread in climates where daily temperatures exceed the optimal thermal range of this species.